2021
DOI: 10.3390/mti5120084
|View full text |Cite
|
Sign up to set email alerts
|

How Can Autonomous Vehicles Convey Emotions to Pedestrians? A Review of Emotionally Expressive Non-Humanoid Robots

Abstract: In recent years, researchers and manufacturers have started to investigate ways to enable autonomous vehicles (AVs) to interact with nearby pedestrians in compensation for the absence of human drivers. The majority of these efforts focuses on external human–machine interfaces (eHMIs), using different modalities, such as light patterns or on-road projections, to communicate the AV’s intent and awareness. In this paper, we investigate the potential role of affective interfaces to convey emotions via eHMIs. To da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Evidently, calibrating trust in the interface, i.e., adjusting trust to match its actual trustworthiness, is essential if it is to ever reach its full performance potential in real-world traffic [157,158]. Considering that trust mediates automation acceptance, it becomes all the more important to allay skepticism and hesitation regarding eHMIs, especially during the familiarization phase, so that the public fully benefits from autonomous vehicle technology [159][160][161][162][163][164]. Previous work has shown that anthropomorphizing an interface ensures that greater trust is placed in it [155,[165][166][167].…”
Section: Trust and Acceptancementioning
confidence: 99%
“…Evidently, calibrating trust in the interface, i.e., adjusting trust to match its actual trustworthiness, is essential if it is to ever reach its full performance potential in real-world traffic [157,158]. Considering that trust mediates automation acceptance, it becomes all the more important to allay skepticism and hesitation regarding eHMIs, especially during the familiarization phase, so that the public fully benefits from autonomous vehicle technology [159][160][161][162][163][164]. Previous work has shown that anthropomorphizing an interface ensures that greater trust is placed in it [155,[165][166][167].…”
Section: Trust and Acceptancementioning
confidence: 99%
“…The shared-control wheelchair employs a semi-autonomous control mode where the user and the autonomous system collaboratively determine the final motion of the wheelchair, aiming for a safer, more efficient, and comfortable driving experience [36,37]. The shared-control wheelchair will transfer part of the driving rights to the autonomous system.…”
Section: Shared-control Wheelchairmentioning
confidence: 99%
“…The results suggested that speed and driving behaviour have a larger impact on pedestrian reactions than the physical appearance of the car. Wang et al [79] examined how AVs could convey emotions to pedestrians, suggesting that the AV should combine emotional displays with movement cues, be not just proactive but responsive, and consider contextual and environmental information, e.g., the weather. AVs could share data with each other and react faster than humans, allowing them to move in highly coordinated formations.…”
Section: A Driving Style Adaptationmentioning
confidence: 99%